The small molecule ZY-214-4 may reduce the virulence of Staphylococcus aureus by inhibiting pigment production - Jingyi Yu; Lulin Rao; Lingling Zhan; Bingjie Wang; Qing Zhan; Yanlei Xu; Huilin Zhao; Xinyi Wang; Yan Zhou; Yinjuan Guo; Xiaocui Wu; Zengqiang Song; et al. (BMC Microbiology, 2021)
Abstract Background In recent years, clinical Staphylococcus aureus isolates have become highly resistant to antibiotics, which has raised concerns about the ability to control infections by these organisms. The aim of this study was to clarify the effect of a new small molecule, ZY-214-4 (C19H11BrNO4), on S. aureus pigment production. Results At the concentration of 4 μg/mL, ZY-214-4 exerted a significant inhibitory effect on S. aureus pigment synthesis, without affecting its growth or inducing a toxic effect on the silkworm. An oxidant sensitivity test and a whole-blood killing test indicated that the S. aureus survival rate decreased significantly with ZY-214-4 treatment. Additionally, ZY-214-4 administration significantly reduced the expression of a pigment synthesis-related gene (crtM) and the superoxide dismutase genes (sodA) as determined by real-time quantitative polymerase chain reaction (RT-qPCR) analysis. ZY-214-4 treatment also improved the survival rate of S. aureus-infected silkworm larvae. Conclusions The small molecule ZY-214-4 has potential for the prevention of S. aureus infections by reducing the virulence associated with this bacterium.